Gaya Bahasa Perbandingan Dalam Syair Muqawwamat “Risalah Min Al-Mu’taqil” Karya Samih Al-Qashim - Fatihin, Muh Khairul; Said, Moch. (Universitas Muhammadiyah Gorontalo, 2024)
Comparative language style is a phenomenon of using language which always juxtaposes two objects as media of parables even though they have different conditions and existence. As for this research, it aims to represent what language styles and their functions are contained in the poem